Politeness and request strategies in Libyan postgraduate students’ e-mails / Ergaya Ali Gerair Alsout - Ergaya Ali , Gerair Alsout (2018)
This study aimed primarily to explore the politeness phenomenon in e-mail requests written by international Post Graduate students from Libya as a means of communicating with their lecturers in four selected Malaysian universities; namely Universiti Utara Malaysia, Universiti Putra Malaysia, Universiti Kebangsaan Malaysia and University of Malaya. The data consisted of 109 e-mails written to their lecturers by 20 Libyan PG students who were studying in Malaysia. To fulfill the objectives of this study, the e-mails were analysed by adopting politeness theory of Brown and Levinson (1987) which acted as the main framework for identifying the politeness strategies. Additionally, Economidou-Kogetsidis’s (2011) framework, known as Cross Cultural Speech Act Realization Project (CCSARP) was used to identify the directness level of request head acts. The internal/external modifications that were evident in the e-mails were also analysed by using the CCSARP framework. The research method and design used in this study was essentially qualitative approach. The findings of the current study revealed that the Libyan PG students applied mostly negative politeness sub-strategies more than the other politeness sub-strategies. Direct strategies also appeared more frequently than conventionally indirect strategies. These students in Malaysian universities were seen to resort to external modifications in greater frequency possibly to minimize the force of their request imposition. The most used internal modification was the politeness marker ‘please’. This study argues that e-mails which lacked internal modifications, and featuring a high level of directness, displayed a fundamental inadequacy in the use of politeness strategies, thus creating potentially a higher chance of pragmatic failure